Pentingnya Memilih KB yang Tepat untuk Keluarga Sejahtera di Posyandu Edelweiss Wilayah Kerja Puskesmas Baloi Permai Batam Kota - Aminah Aatinaa Adhyatma; Dinda Aprilia Putri; Tiara Putri; Siti Nurlela (Jurnal Surya Masyarakat, 2022)
The family planning (KB) program is one of the government programs organized to limit births to reduce population growth. The purpose of this community service is to improve the family planning program in an effort to regulate the birth of children, distance, and the ideal age of childbirth, regulate pregnancy, through promotion, protection and assistance in accordance with reproductive rights to create a quality and prosperous family. This community service method is carried out by conducting socialization, counseling, and health promotion to 26 couples of childbearing age at the Edelweiss Posyandu Working Area of the Baloi Permai Health Center, Batam City, Riau Islands. This counseling uses measuring instruments by taking data directly from respondents through filling out pre-test and post-test checklist sheets that have been distributed to participants.  Various contraceptives were also explained to 26 couples of childbearing age, namely natural birth control, pills, injections and long-term birth control. This counseling was carried out at the Edelweiss Posyandu working area of the Baloi Permai Health Center, Batam City, Riau Islands, on Tuesday, June 28, 2022, which was attended by 26 couples of childbearing age by producing an increase in pus knowledge and insight. It can be concluded that the community at the Edelweiss Posyandu was enthusiastic by giving questions and did not die from the community service counseling site.